RELATIONSHIP BETWEEN ACTIVE PHYSICAL EXERCISE AND SLEEP QUALITY WITH PHYSICAL FATIQUE IN ELDERLY ON HARAPAN BARU SAMARINDA PUBLIC HEALTH CARE - Ramdhany Ismahmudi; Alfi Ari Fakhrurizal (Universitas Muhammadiyah Kalimantan Timur, 2020)
Physical excercise is any form of activity carried out by an individual, especially the elderly, in an effort to improve physical fitness and physical conditions, with the main objective being to increase strength, cardiorespiration endurance, speed, skills and flexibility. In the elderly, physical training aims to improve the quality of life, so they can get through their old days in a fit. The purpose of this study is to find out how the relationship between active physical activity and sleep quality with physical fatigue that occurs in the elderly in the working area of the Harapan Baru Health Center in Samarinda City. This research is a descriptive qualitative study using a cross sectional study approach. Sampling is done by the method of Total Sampling, where all respondents will be involved for research activities, with a total sample of 125 respondents. Data collection techniques using interview techniques, observation, and research questionnaires. Data processing and analysis using univariate analysis using frequency distribution tables for the description of the study, and multivariate analysis using chi-square analysis. The research activity was carried out for approximately 1 month starting from July 23-August 24, 2019 at the Harapan Baru Health Center in Samarinda. Based on the results of tabulation of data conducted using univariate analysis for physical activity variables showed that the majority of respondents were in the high category with 71 respondents (57%), for the sleep needs of 125 respondents showed the majority in good sleep needs with the number of respondents as many as 68 people (54%), and for the variable physical fatigue the majority of respondents were in the category of Tired with the number of respondents as many as 72 people (58%). For bivariate analysis between physical activity with fatigue where 43 of 71 respondents (34%) did not experience fatigue after doing physical activity, with a P-Value of 0.025 <0.05, so that there was a significant relationship between physical activity. with fatigue, and the OR value = 2,298 shows that the elderly who are active in physical activity will not experience physical fatigue. For the sleep needs variable of 39 people (31%) of respondents with sleep deprivation problems do not experience fatigue, with a P-Value of 0.442> 0.05, so there is no significant relationship between sleep needs and fatigue of an elderly person. With OR value = 0.755 where elderly people who have adequate sleep will not experience physical fatigue.